The Role of Think-Pair-Share in Enhancing Writing Skills in Recount Texts - Arief Zul Fauzi (CV. Eureka Murakabi Abadi, 2024)
This research investigates the effectiveness of the Think-Pair-Share (TPS) strategy in improving the writing skills of first-year students at a Polytechnic in Tegal, focusing on Recount Texts. As a quantitative study, the research evaluated the students’ progress through three stages of testing: pre-test, Cycle 1 test, and Cycle 2 test (post-test). The study aimed to measure the impact of TPS on students’ writing performance, particularly in content organization, grammar, and coherence. A total of 25 students participated in the study, with their performance assessed at each stage. The average scores consistently improved: 69.24 on the pre-test, 74.36 on the Cycle 1 test, and 86.08 on the Cycle 2 test. This progression highlights the effectiveness of TPS in guiding students through a structured process of brainstorming, collaboration, and drafting. The results indicated that the Think phase helped students generate and organize ideas, the Pair phase encouraged constructive peer feedback, and the Share phase facilitated the development of cohesive and polished narratives. The findings demonstrate the potential of TPS as an effective strategy for enhancing writing skills in collaborative learning environments. By providing measurable improvements in writing performance, this study offers valuable insights for educators seeking to implement structured, student-centered approaches to teaching writing. Future research could expand on these findings by exploring the application of TPS to other writing genres or different educational contexts.